In vitro effects of the combination of serotonin, selenium, zinc, and vitamins D and E supplementation on human sperm motility and reactive oxygen species production - Yilmazer, Yasemin; Moshfeghi, Elnaz; Cetin, Fadime; Findikli, Necati (CAMBRIDGE UNIV PRESS, 2024)
Infertility affects 15% of all couples worldwide and 50% of cases of infertility are solely due to male factors. A decrease in motility in the semen is considered one of the main factors that is directly related to infertility. The use of supplementation to improve the overall sperm quality has become increasingly popular worldwide. The purpose of this study was to evaluate whether sperm motility was affected by the combination of serotonin (5-HT), selenium (Se), zinc (Zn), and vitamins D, and E supplementation. Semen samples were incubated for 75 min at 37 degrees C in medium containing varying concentrations of 5-HT, Se, Zn, vitamin D, and E. 5-HT (200 mu M), Se (2 mu g/ml), Zn (10 mu g/ml), vitamin D (100 nM), and vitamin E (2 mmol) have also been shown to increase progressive sperm motility. Three different mixtures of supplements were also tested for their combined effects on sperm motility and reactive oxygen species (ROS) production. While the total motility in the control group was 71.96%, this was found to increase to 82.85% in the first mixture. In contrast the average ROS level was 8.97% in the control group and decreased to 4.23% in the first mixture. Inclusion of a supplement cocktail (5-HT, Se, Zn, vitamins D and E) in sperm processing and culture medium could create an overall improvement in sperm motility while decreasing ROS levels during the incubation period. These molecules may enhance the success of assisted reproduction techniques when present in sperm preparation medium.
Keywords: Infertility; Serotonin; Sperm motility; Sperm-wash medium; OXIDATIVE STRESS; SWIM-UP; 5-HYDROXYTRYPTAMINE; PHOSPHORYLATION; LOCALIZATION; Cell Biology; Developmental Biology; Reproductive Biology